Broadly steerable parasitic patch array antennas using pin diode switches at 5.8 GHz - Thennarasan Sabapathy (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2014)
In this thesis, thorough investigation on parasitic patch array antenna with actual RF switches is conducted with two types of RF PIN diodes, namely BAR50-02V and HPND-4005.